Outcome of cataract surgery in central India: a longitudinal follow-up study. Issue 2 (February 1991) - Reidy, A; Mehra, V; Minassian, D; Mahashabde, S
Abstract : An epidemiological follow-up study of patients who had intracapsular cataract extraction in a voluntary hospital and its associated eye camps in Central India has for the first time evaluated the outcome one year after surgery in terms of visual acuity, use of spectacles, and improvement in income and mobility. The findings indicate that under these fairly typical conditions, 92% of the cases have adequate vision of 6/18 or better one year after surgery. Information on high usage of spectacles and on considerable improvements in income and mobility after cataract surgery is also reported. The outcome for patients operated upon in eye camps was almost as favourable as for those operated upon in hospital. Although the small differences are not statistically significant, the comparative findings require cautious interpretation and give rise to the epidemiological issues which are briefly discussed in this paper.